Joined fragment segmentation for fractured bones using GPU-accelerated shape-preserving erosion and dilation. - Zhang, Yue; Tong, Ruofeng; Song, Dan; Yan, Xiaobo; Lin, Lanfen; Wu, Jian (Medical & Biological Engineering & Computing, 2020)
Joined fragment segmentation for fractured bones segmented from CT (computed tomography) images is a time-consuming task and calls for lots of interactions. To alleviate segmentation burdens of radiologists, we propose a graphics processing unit (GPU)-accelerated 3D segmentation framework requiring less interactions and lower time cost compared with existing methods. We first leverage the normal-based erosion method to separate joined bone fragments. After labeling the separated fragments via CCL (connected component labeling) algorithm, the record-based dilation method is eventually employed to restore bone's original shape. Besides, we introduce an additional random walk algorithm to tackle the special case where fragments are strongly joined. For efficient fragment segmentation, the framework is carried out in parallel with GPU-acceleration technology. Experiments on realistic CT volumes demonstrate that our framework can attain accurate fragment segmentations with dice scores over 99% and averagely takes 3.47 s to complete the segmentation task for a fractured bone volume of 512 × 512 × 425 voxels. We propose a GPU accelerated segmentation framework, which mainly consists of normal-based erosion and record-based dilation, to automatically segment joined fragments for most cases. For the remaining cases, we introduce a random walk algorithm for segmentation with a few interactions.